Method of Processing Oil Palm Frond into Biomass Fuel for Downdraft Gasification - Moni, M. N. Z. (2012)
A recent study in the downdraft gasification of oil palm fronds (OPF) in Malaysia showed that it has a high potential as a biomass fuel mainly due to its abundance and relatively good fuel properties. However, the method of processing OPF into quality fuel has yet to be studied and established. Green and brown OPF were studied for their potentials as biomass fuel and their properties as fuel were investigated. It was found that only green OPF was suitable to be processed into fuel due to its uniformed tissue integrity and physical strength. The selection, sizing, drying and storing process of OPF fuels were also investigated, showing potent results where, in order to qualify as a quality fuel for gasification, green OPF must be in the size of 2.5-5.0 cm cubic blocks or 2.5-5.0 cm long and 0.25-0.50 cm thick chips with moisture content of 10-20%. The storage area must be dry and free from humidity in order to keep the equilibrium moisture content of OPF fuel to lower than 15% for instorage drying and to control its hygroscopic activity.